The Influence of Green Marketing, Brand Awareness, And Lifestyle on the Purchase Decision of Aqua Life Bottled Water Products in Surabaya - Maharani, Kirana Aurelia Julianne; Purwanto, Sugeng (East Asian Journal of Multidisciplinary Research, 2024)
The progress of the bottled water industry has resulted in fierce competition, resulting in many findings of plastic waste in the form of bottled water product packaging. The large number of plastic waste findings increases the amount of waste accumulation that causes environmental damage. The change in environmentally friendly lifestyle is starting to occur, because there is concern in the community about the problem of environmental corruption. This study aims to determine the influence of green marketing, brand awareness, and lifestyle on consumer purchasing behavior. The population of this study is the people of Surabaya who have purchased Aqua Life bottled water products with a sample of 102 respondents. The research methodology used is non-probability sampling, especially using convenience sampling. Data was collected through G-form and data analysis involved a partial least square (PLS) approach. The results of the study obtained a positive, but not significant relationship between green marketing and purchase decisions. Brand awareness and lifestyle were found to have a positive and significant influence on the purchase decision of Aqua Life bottled water products in Surabaya.